POTENSI GAS RUMAH KACA (GRK) KOLAM ANAEROBIK PADA PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT (LCPKS) - Hisyam Musthafa Al Hakim; Lya Agustina (EnviroScienteae, 2018)
World vegetable oil needs to be increased every year along with population growth. Vegetable oil which potential to supply is palm oil because it has the highest productivity compared to other vegetable oil sources. Behind the rapid development of palm oil, came negative issue about environmental damage especially the increase of greenhouse gas emissions caused by the palm oil industry. This research aimed to calculate the potential of greenhouse gas caused by palm oil mill effluent (POME) treatment in the anaerobic pond. The method used is by capture methane and carbon dioxide at the float chamber then gas chromatography analyzed. The results showed that the highest methane and carbon dioxide released at night (10.00 – 11.00 pm). The average potential released methane is 9441.28 mg C-CH4 m-2h-1 and Carbon dioxide is 5920.74 mg C-CO2 m-2h-1.